National spirit in modern kazakh poetry. (Eurasian Journal of Philology Science and Education, 2015)
The innovation of modern Kazakh lyrics, the loudspeaker and statics of modern poetry presents spirit to a civic stand of representatives of modern poetry in article special interest, national. In article it is analyzed the new directions of modern Kazakh lyrics, creativity of figures with scientific, literary теоритической the points of view. Reflection of tradition and innovation in a new era was analyzed. The main objective of this article – to open an image of creativity of eminent persons of modern Kazakh lyrics, to reveal innovation, peculiar features of modernlyrics, to designate a place of works in the history of the Kazakh literature.In this article creativity of such poets as Қалқаман Sarin, A
Keywords: national spirit; Kazakh poetry; civic stand; innovation; national consciousness